Co-gasification of pine and oak biochar with sub-bituminous coal in carbon dioxide. (March 2018) - Beagle, E.; Wang, Y.; Bell, D.; Belmont, E.
Highlights: Gasification of pine and oak biochars alone and blended with sub-bituminous coal. Modified drop tube reactor used to assess gasification time and kinetics in CO2 . Modified drop tube and thermogravimetric reactors used to assess fuel interactions. Synergy Index (SI) used to assess non-additive behavior in fuel blend gasification. Inhibitory behavior observed in all fuel blends, and SI varies with temperature. Abstract: Pine and oak biochars derived as byproducts of demonstration-scale pyrolysis, and blends of these two feedstocks with Powder River Basin coal, were gasified in a carbon dioxide environment using a modified drop tube reactor (MDTR) and a thermogravimetric analyzer (TGA). The impact of gasification temperature on conversion kinetics was evaluated from the temporal evolution of major product gases in the MDTR as measured using a mass spectrometer. Random pore modeling was conducted to simulate gasification in the MDTR with favorable results. The MDTR and TGA were used to conduct gasification for assessment of non-linear additive effects in the blends. Additive analysis of the blends showed deviation from the experimental blend results, indicating inhibiting effects of co-gasifying the biochar and coal. Inhibitory effects are more significant for oak than pine and more pronounced in the TGA at lower gasification temperatures. Results are discussed in the context of feedstock and reactor type.